Tangible interface for shape modeling by block assembly of wirelessly connected blocks. Issue 4 (16th April 2019) - Son, Jinwon; Jang, Hoik; Choi, Young
Graphical abstract: Abstract: Tangible computer-aided design (CAD) that can generate and manipulate 3D models more efficiently than conventional modeling interfaces is a new interface technology between users and computers through tangible physical devices. Because the majority of tangible CAD systems use cameras or projectors, 3D models of complex structures with visual occlusion cannot be generated. In this work, we propose and develop a system that allows users to create complex shapes by assembling wireless blocks. By allowing more freedom in the orientations of blocks, models created by the assembly operation can be used to generate true 3D shapes compared to the 2.5D shapes resulting from previous research. The physical blocks of the proposed system include infrared proximity sensors, inertial magnetic units, Zigbee modules, and Arduino microcontrollers. The status of the block assembly is transmitted to the workstation wirelessly by the Zigbee. The workstation collects the sensor data of the blocks and generates and renders 3D models of the physically assembled blocks. The concept of the proposed tangible CAD system can be used in various application areas where simple, easy-to-use shape modeling interfaces for creating models by assembling small blocks are sufficient. The education and gaming industries are good examples of where this concept can be applied easily.